The Effect of Digital Breast Tomosynthesis on BI-RADS Categorization in Different Breast Densities: A Retrospective Evaluation - Tekcan Şanlı, Deniz Esin; Aksu, Emre; Şanlı, Ahmet Necati; Turan, Bilal (The European Research Journal, 2026)
Objective: This study aimed to evaluate the impact of digital breast tomosynthesis (DBT) on BI-RADS categorization compared to conventional mammography (MMG), across different mammographic breast density types. Methods: In this retrospective study, 520 female patients aged 35–85 years who underwent both MMG and DBT between 2023 and 2025 were included. Standard craniocaudal (CC) views were acquired for MMG and mediolateral oblique (MLO) views for DBT. Synthetic MLO (sMLO) images were automatically generated by the device from DBT data. Patients were categorized according to the breast density (Type A–D), and all images were reviewed in consensus by two experienced radiologists. Breast Imaging Reporting and Data System (BI-RADS) categories, lesion types, were recorded. BI-RADS categorizations from MMG and DBT were compared overall and within density subgroups. Results: The mean age was 53.0 ± 9.9 years. Breast density distribution was: Type A (3.8%, n=20), B (28.5%, n= 148), C (43.5%, n=226), and D (24.2%, n=126). BI-RADS classifications differed significantly between MMG and DBT, especially in dense breasts. Of the BI-RADS 2 cases on MMG, 21.6% (n=64) were reclassified as BI-RADS 3 or 4 with DBT, while 6.3% (n=7) of BI-RADS 3 cases were downgraded. BI-RADS 5 categorization showed complete agreement between modalities, though 33% (n=5) of BI-RADS 4 cases were downgraded. At least one pathological finding was observed in 91.3% (n=475) of patients, most commonly nodular opacities (57.1%, n=297), vascular wall calcifications (13.3%, n=69), and coarse calcifications (5.4%, n=28). McNemar analysis revealed significant reclassification between BI-RADS 2 and 3 in Types C and D (P<0.001). Conclusion: DBT significantly alters BI-RADS categorization in dense breasts. These findings support the potential role of DBT as a complementary tool in screening protocols, particularly for patients with heterogeneously dense or extremely dense breast tissue.